(untitled) (Journal of Hama University, 2024)
The aim of the research is to identify the attitudes of the students of the Faculty of Physical Education at Tishreen University towards recreation and leisure time. The data was prepared by Al-Hamamy (2013), and the scale consisted of (62) phrases, distributed on four dimensions (the trend towards the concept of leisure time, the trend towards the concept of recreation, the trend towards the return from recreation, the trend towards socialization). The researcher concluded that the attitude of the students of the College of Education There are no statistically significant differences between the attitudes of students of the Faculty of Physical Education at Tishreen University due to the gender variable.